How can we make carbon nanotube yarn stronger?. (29th September 2018) - Jung, Yeonsu; Cho, Young Shik; Lee, Jae Won; Oh, Jun Young; Park, Chong Rae
Abstract: There has been remarkable progress with regard to the fabrication of yarns based on high-performance carbon nanotubes (CNTs). However, the theoretically predicted tensile strength of CNTs has yet to be realized in practical CNT yarns or CNT-reinforced composites. Having considered that there are few systematic guidelines for preparing high-strength CNT yarns, we attempted to revisit the-state-of-the-art progress in the theories and yarn formation processes of CNT yarns and then draw possible correlations between the intrinsic and extrinsic structural parameters of elementary CNTs, yarn formation processes and the tensile strength of the resulting CNT yarns. On the basis of these considerations and discussions of advanced technologies and theoretical approaches, possible routes to improve the strength of CNT yarns further are suggested.